2018
DOI: 10.1364/ao.57.000154
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive three-dimensional ray tracing model for three-mirror cavity-enhanced spectroscopy

Abstract: A 3D ray tracing model is used to simulate optical reinjection in a nonresonant optical cavity, for off-axis integrated cavity output spectroscopy. The optical cavities are optimized for maximum intensity enhancement factors via a grid search and a genetic algorithm. Intensity enhancement factors up to 1400 are found for short cavities (3 cm) and up to 101 for long cavities (50 cm). The model predicts that short absorption cells can be used, having a long effective path length and a high throughput power. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
(44 reference statements)
1
10
0
Order By: Relevance
“…By using a re-injection mirror, the output intensity can be increased above the noise floor of the detector. From our model, it is shown that improved enhancements can be achieved by using shorter cavities with larger diameters [30]. This will trigger new opportunities in the field of ultrasensitive gas detection using compact optical gas sensors with a small footprint.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…By using a re-injection mirror, the output intensity can be increased above the noise floor of the detector. From our model, it is shown that improved enhancements can be achieved by using shorter cavities with larger diameters [30]. This will trigger new opportunities in the field of ultrasensitive gas detection using compact optical gas sensors with a small footprint.…”
Section: Discussionmentioning
confidence: 87%
“…6). This might be due to the fact that distance between the re-injection mirror and the first absorption cavity mirror is equivalent to the focal length of the re-injection mirror [30]. At d ∕R 0.6, an ellipse consisting of 39 roundtrips (laser beam entrance angles α x −0.4°, α y −0.6°in the x, y direction) is found, which corresponds to a maximum enhancement factor of 38.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By comparing the decay time of the empty cavity with that of the cavity filling with measured gas, the absorption coefficient can be obtained. Since the ring-down procedure occurrs in a fairly short period, CRDS highly depends on fast-response detection electronics, which limits its application [12,13]. Besides, the spectral resolution of CRDS is relatively low due to the use of pulsed lasers.…”
Section: Introductionmentioning
confidence: 99%